THE CORRELATION BETWEEN LANDUSE CHANGES WITH ROAD DENSITY IN URBAN FRINGE SOUTH SURAKARTA - Dewangga Megaloka Putri; Kuswanto Nurhadi; Erma Fitria Rini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2016)
From time to time the poplulation growth effect on the needs-of-lands. The growth of the city affect the changes of the sub-urban in a phisycal and activities. It arises as a result from the need-for-land that already not able to be fullfiled by the city Itself. Eventually, lands in the sub-urban transformed which previously dominated by non-built-up land  turn into built-up land. The movements from sub-urban to city also increased. The feeder roads between sub-urban and the city gets more dense. The study aims to review developments on the land use and density of roads in the period of time between 2010 Until 2016 and the correlation between land use development and density of roads. This research is using deductive method and ordinal regression analysis techniques. The datas that be used are primary data obtained through field observation and secondary data through study documents. The result shows the correlation between the land use development and density urban roads in the South urban fringe in the Surakarta city